The use of object-oriented programming in the study of the position of Muslims in the social space of the Kingdom of Castile and Leon (XIII-XV centuries) - Sidorovich, Ekaterina Andreevna (Историческая информатика, 2025)
The object of this study is the social history of the Kingdom of Castile and Leon in the 13th–15th centuries, which covers the dynamics of interactions between religious communities and their legal, economic and social status. The subject of the study is the application of object-oriented programming based on the example of using the unified modeling language (UML) to analyze the position of Muslims in the social space of the Kingdom of Castile and Leon of the specified period. The purpose of the article is to explore the possibilities of using UML in historical science, demonstrating how this method contributes to the modeling of social and legal structures of the past, as well as the structuring of historiographical concepts explaining the problem of coexistence in medieval Spain. The research aims to use engineering methods in studying the social and economic role of the Muslim population in the context of interaction with Christians and Jews. The research methodology combines traditional historical methods with modern programming approaches, which allows for a deeper understanding and analysis of the social status of Muslims and theoretical concepts about their role in the Kingdom of Castile and Leon. The author conducted a comprehensive analysis of the academic literature justifying the use of UML in the humanities. The scientific novelty lies in the use of class diagrams to analyze the social status of Muslims in the Kingdom of Castile and Leon in the 13th–15th centuries. This modeling language allows to structure complex social relationships, reflect the hierarchy of social groups, their legal status and relationships. UML is also effective for systematizing historiographical material, helping to identify hidden relationships between concepts. At the same time, this language is not a familiar tool for historians, which may make it difficult for researchers to use it. Nevertheless, mastering the syntax of these diagrams can be promising when modeling social relations. In addition, the use of UML promotes the integration of interdisciplinary approaches, combining methods of historical science and computer science.